Challenges faced by classroom teachers in multigrade classrooms: A case study - Barış Kalender; Erol Erdem (Journal of Pedagogical Research, 2021)
The aim of this study is to identify the main problems that arise in multigrade classrooms. This research was designed as a case study. The data were obtained through interviews and observations. Participants of the study consist of 10 teachers working in multigrade classrooms in a district in the Mediterranean region in Turkey. The data were analyzed by using thematic analysis. As a result of the research, it was found out that the teachers were left alone in the multigrade classrooms and had difficult times. It was determined that they had problems in planning and executing the learning-teaching process, as well as ensuring classroom management. It was also revealed that having the duty of a principal teacher was a heavy burden for teachers and this duty led them to do all kinds of work at schools. It was discovered that the inspections made by the Ministry of National Education did not contribute greatly to teachers. However, parental assistance to teachers in non-educational matters appeared to be the only support for them within their daily workload.